Self-efficacy among students participating in martial arts and team sports extracurricular activities: a comparative study - Prasascita Qolbu; Hamdani Hamdani (Universitas Sriwijaya, 2026)
Research Problems: Martial arts and team sports provide different psychological and social learning experiences that may contribute to students’ self-efficacy. However, evidence regarding whether participation in these two types of extracurricular sports leads to differences in students’ self-efficacy remains limited and inconclusive. Research Objectives: This study aimed to compare the self-efficacy of students participating in martial arts and team sports extracurricular activities. Methods: This study employed a quantitative non-experimental approach using a comparative research design. A total of 115 students actively participating in sports extracurricular activities were selected as the research sample. Data were collected using a self-efficacy questionnaire adapted from a previously validated and reliable instrument based on Bandura’s self-efficacy theory, covering the dimensions of level, strength, and generality. The data were analyzed using descriptive statistics, the Kolmogorov–Smirnov normality test, and the Mann–Whitney U test. Results: The findings indicated no statistically significant difference in self-efficacy between students participating in martial arts and those participating in team sports extracurricular activities (p = 0.870 > 0.05). This result suggests that students in both groups demonstrated comparable levels of self-efficacy. Conclusion: Participation in martial arts and team sports extracurricular activities was associated with similar levels of self-efficacy among students. These findings indicate that the type of extracurricular sport alone may not explain differences in students’ self-efficacy. Future research should investigate additional factors, such as motivation, training intensity, and social support, to better understand the determinants of self-efficacy in sports participation.